Evaluation of Modified Nanoparticles' Effects on Polypropylene Composites - Haydar U. Zaman; Ruhul A. Khan2 (International Journal of Pollution: Prevention & Control, 2024)
Numerous sectors use nanoparticles and nanocomposites in a range of applications, including medicine, textiles, cosmetics, agriculture, optics, food packaging, optoelectronics, semiconductors, aerospace, building materials, and catalysis. Polymeric nanocomposites, which combine organic polymers with inorganic nanoparticles, are a novel family of materials that perform better than their microparticle counterparts. They should therefore enhance the field of engineering applications. A polymer matrix's characteristics can be drastically changed by the addition of inorganic nanoparticles. Nanoparticle reinforced polymer flexible composites, such as titanium dioxide (nTiO2) and zinc oxide (nZnO), open up new design possibilities with superior mechanical and chemical properties. This study examined the mechanical characteristics, morphological and thermal properties of composites made of polypropylene (PP) and filled with nTiO2 and nZnO. There were between 1 and 5 weight percent of nanoparticles in the matrix. Prior to melt mixing, silane and maleic anhydride-grafted styrene, ethylene butylene styrene (SEBS-g-MA) were applied to nanoparticles to improve fine dispersion and surface adherence. A twin-screw extruder and a heat press were used to create PP/nanoparticle nanocomposites in order to study the impact of modified and unmodified nanoparticles at various concentrations on the mechanical characteristics, morphological and thermal properties. Since nanoparticles have a rigid structure, all tensile properties-including yield strength, tensile strength, and tensile modulus-have increased while impact strength and elongation at break have decreased. Because of this, nanocomposites containing nTiO2 exhibited more elongation than those containing nZnO, despite nTiO2 having a higher hardness than nZnO. In comparison to SEBS-g-MA, the presence of silane in the PP/nTiO2 nanocomposite was more productive. The tensile characteristics of silane-modified nTiO2 nanocomposites, however, were higher than those of silane- modified nZnO nanocomposites. In this instance, the more refined structure of nTiO2 with PP has been induced, which ensures the outcome of reduced elongation at break. This is likely due to the superior compatibility of nTiO2 with silane. Thermal analysis was also carried out to determine the melt temperature, crystallization temperature, and crystallinity level.
Keywords: Mechanical properties; Morphology; Nano-TiO2; Polypropylene; nano-ZnO; nanocomposites